Clinical Utility of Psychoeducational Interventions for Youth with Type 1 Diabetes: A Scoping Review. Issue 1 (15th July 2021) - Bergmame, Lana; Shaw, Steven
Adolescence is a challenging time for the medical management of type 1 diabetes. Thus, a range of psychoeducational interventions have been developed to improve diabetes management among youth. Systematic reviews of this literature have emphasized the effectiveness of interventions for improving patient outcomes. However, knowledge beyond what works is required for interventions to be adopted into routine clinical practice. The objective of this scoping review was to map the clinical utility of the literature based on a variety of indicators, including the problem base, context placement, information gain, transparency, pragmatism, and patient-centeredness of the research. This lens for reviewing research is consistent with the biopsychosocial model and an increasing focus on reducing disability, including activity limitation and participation restriction. PsycINFO, MEDLINE, and CINHAL databases were searched for evaluative psychoeducational intervention studies published between January 2005 and October 2020. Two cited reference searches and one reference list search were also performed. Fifty studies describing 46 different interventions were identified. The clinical utility of the interventions was highly variable. A detailed overview of the clinical utility of the literature is provided with an emphasis on current gaps and shortcomings to be addressed in future research. This work helps advance the translation of clinical knowledge into practice in schools, homes, and communities; and, ultimately, improve the health and well-being of adolescents with T1D.